Establishment of rainfall erosivity calendar at main cities of peninsular Malaysia / Nur Zarina Zakaria - Zakaria, Nur Zarina (2007)
Malaysia in its rapid growing of development is undergoing tremendous land use changes especially in the development of infrastructure. Although this activity forms an important role to the intergral part of the socio-economic advancement in the country, the unpleasant effects of land development, particularly soil erosion will certainly jeopardize its success. Soil erosion has become a very serious problem in Malaysia recently and it is one of the natural processes that occur on earth. With the accelerated land development both in public and commercial sectors, this problem will certainly persevere and deteriorate unless proper planning and management of land utilization is adopted at the early stage of any future land development. The fact that soil erosion continue to be an environmental problem and of significant impact in the country suggest that more definitive guidelines and stem monitoring of land development are required. Therefore. This research will focus on recognizing the rainfall induced erosion risk occurrence since rainfall is one of the significant factors is causing soil erosion that can leads to landslide to major cities in Peninsular Malaysia. Thus, evaluation of rainfall erosivity profile at the main cities of Peninsular Malaysia namely Alor Setar, Georgetown, Kuala Lumpur, Johor Bahru, Kuantan and Kuala Terengganu would be tangible contribution to the various states government in tackling problems to soil erosion issues. Research outcomes indicate that different cities reveals different results namely the monthly rainfall amount, erosion risk frequency, percentage of rainfall erosivity potential as well as the degree of values of rainfall erosivity. As in the case of the most risky months, months of October, November and December recorded the highest number of occurrence based on the accumulated degree of 7 days rainfall amount. Further results reveal that the most risky city with regards to rainfall erosivity corresponding to high, very high and critical degree 0f“ROSE” Index is Kuala Lumpur while the less risky city is Kuala Terengganu. The results indirectly confirm the severity of erosion induced erosion at Kuala Lumpur city based on historical records as well as the present scenario. This research is also useable in other areas in Malaysia in order to determine the risky and safest areas with regards to rainfall induced erosion which can leads to landslide.